The Influence of Smes on the Leisure and Tourism - Anca Gabriela Turtureanu; Cornelia Elena Tureac; Aurica Grigore (EIRP Proceedings, 2009)
The leisure is a component of standard of living and quality of life, expresses the level of materialand spiritual life, without it can’t be held the multilateral development of the human, enforcing recoveryfunctions of the organism, formative and instructive – educative, cultural and social. In pre-modern times, thefree time was located on religious holidays and in the rest days established on the basis of religion (Sunday atChristians, Saturday at Jews, etc.) The good of the individual towards trends any true democracy has in itsstructure, along with the material components and social and spiritual. In the economic and social framework,the reproduction of material conditions of existence is doubled by the health care, intelligent, creative force ofthe society members